The Effect of Iraqians High Environmental Temperature on Growth Performance in Two Lines of Japanese Quail - Aljumaily, Tareq KH. (International Journal of Poultry Science, 2011)
This study was conducted to investigate the potential effect of Iraqians High Environmental Temperature on Growth Performance in two lines of Japanese quail. Four-hundred eighty mixed 1-day old chicks were randomly assigned to 12 replicates of 20 chicks per replicate for each strain. The birds were exposed to ambient Iraqi environmental conditions. The average daily high temperature during the experimental period, averaged 30°C ranging between 24-36°C. The results showed that there was Brown strain had higher body weight than those white strain. Feed intake level of White strain and Brown strain and gain day less body weight and had significantly (p